Comparison of the conventional Macintosh laryngoscope, the Pentax Airwayscope, and the McGrath MAC video laryngoscope under restricted cervical motion: a manikin study. Issue 2 (20th October 2014) - Kotera, Atsushi; Irie, Hiroki; Iwashita, Shinsuke; Taniguchi, Junichi; Kasaoka, Shunji; Kinoshita, Yoshihiro
<x xml:space="preserve">Abstract</x> Aim We compared the utility of the conventional Macintosh laryngoscope, the Pentax Airway Scope, and the McGrath MAC video laryngoscope under restricted cervical motion using a manikin. Methods We recruited 36 participants into the simulation study. The manikin's cervical motion was restricted with a cervical collar and a head immobilizer, as occurs in trauma cases. We recorded the time to intubation and the success rate of the intubations. Results Data are medians and ranges. The time to intubation under normal and restricted cervical motion were 22.5 (10–78) and 23 (9–119) s with the Macintosh laryngoscope, 13.5 (5–50) and 14 (7–119) s with the Airway Scope, and 13 (6–32) and 18 (7–80) s with the McGrath MAC video laryngoscope. The differences in the time to intubation between normal and restricted cervical motion were significant only with the McGrath MAC (P = 0.0008). With restricted cervical motion, the times to intubation in the Airway Scope attempts were significantly shorter than those in the Macintosh laryngoscope (P = 0.0005) and McGrath MAC (P = 0.0282) attempts. The success rates under normal and restricted cervical motion were 100% and 80.6% with the Macintosh laryngoscope (P = 0.0054), 100% and 100% with the Airway Scope, and 100% and 97.2% with the McGrath MAC, respectively. Conclusion In the present study, the Airway Scope was the best among the three devices. However, the differences between the Airway Scope and the McGrath MAC video laryngoscope may not be serious in a clinical situation. Data were gathered using a manikin, and further studies will be necessary.